THE USE OF HELLO TALK IN IMPROVING WRITING ABILITY - Kanserini, Julia; Rofiqoh, Rofiqoh; Dewi, Anjar Kusuma; Mashuri, Mashuri (Tadulako University, 2025)
The objectives of this research are to describe how to use HelloTalk in teaching English and to know from the review whether the use of HelloTalk can improve the students’ writing ability. The study applied qualitative research that implemented Library Research Method. The data were collected from scientific writings on the use of HelloTalk in improving writing ability between 2019 and 2024. The findings indicate that HelloTalk can significantly improve students' writing ability by fostering collaboration, creativity, real-time interaction, out-of-class practice, grammar and vocabulary reinforcement, and personalized feedback. HelloTalk is a valuable tool for teachers to enhance English language teaching and promote students' writing development.Teachers are encouraged to integrate HelloTalk into their English language curriculum to leverage its various features and benefits for improving students' writing skills. Further research could explore the long-term effects of HelloTalk on writing proficiency and investigate its potential in different educational contexts.